2012
DOI: 10.1007/s13361-012-0530-8
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry Study of Multiply Negatively Charged, Gas-Phase NaAOT Micelles: How Does Charge State Affect Micellar Structure and Encapsulation?

Abstract: Abstract. We report the formation and characterization of multiply negatively charged sodium bis(2-ethylhexyl) sulfosuccinate (NaAOT) aggregates in the gas phase, by electrospray ionization of methanol/water solution of NaAOT followed by detection using a guided-ion-beam tandem mass spectrometer. Singly and doubly charged aggregates dominate the mass spectra with the compositions of [Na n-z AOT n ] z-(n01-18 and z01-2). Solvation by water was detected only for small aggregates [Na n-1 AOT n H 2 O] -of n03-9. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…The solubilization of small‐sized molecules in gas phase aggregates formed by sodium bis (2‐ethylhexyl) sulfosuccinate (NaAOT) has been investigated by Fang et al In particular, studying the inclusion of some amino acids, these authors observed that their insertion in NaAOT aggregates occurs only above an aggregation number of 8. Moreover, the number of molecules which can be incorporated increases with the aggregate size; up to 5 glycine molecules can be secluded in NaAOT aggregates with aggregation number ≥ 24.…”
Section: Introductionsupporting
confidence: 57%
“…The solubilization of small‐sized molecules in gas phase aggregates formed by sodium bis (2‐ethylhexyl) sulfosuccinate (NaAOT) has been investigated by Fang et al In particular, studying the inclusion of some amino acids, these authors observed that their insertion in NaAOT aggregates occurs only above an aggregation number of 8. Moreover, the number of molecules which can be incorporated increases with the aggregate size; up to 5 glycine molecules can be secluded in NaAOT aggregates with aggregation number ≥ 24.…”
Section: Introductionsupporting
confidence: 57%
“…While for positively charged AOTNa a reverse micelle-like structure has been somewhat agreed by several authors, (Bongiorno et al, 2010;Fang, Bennett, & Liu, 2010 some disagreement emerges for negatively charged aggregates. Fang, Liu, and Liu (2013) have indeed evidenced some peculiarities of negatively charged AOTNa micelles with respect to positively charged aggregates, that more straightforwardly lead to hypothesize a direct micelle-like structure. Most evidences deal with the increased capacity of negatively charged aggregates to host glycine or tryptophan (TRP) molecules.…”
Section: Entrapment Of Solubilizates In Gas Phase Surfactant Aggrementioning
confidence: 79%